2017
DOI: 10.1007/s00592-017-1071-1
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in type 2 diabetes patients: a systematic review of systematic reviews

Abstract: Aim To summarize, critically review, and interpret the evidence related to the systematic reviews on health literacy (HL) amongst type 2 diabetes mellitus (T2DM). Methods The methodology for this study consisted of a systematic review of systematic reviews, using the PRISMA statement and flowchart to select studies, and searching on PubMed, CINAHL, Scopus, and Cochrane. The search covered the period between January 2006 and June 2016. Results From the 115 identified record by the queries, only six systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
79
3
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 47 publications
6
79
3
6
Order By: Relevance
“…In a similar fashion, we found that health literacy was positively related to diabetes knowledge, echoing findings from systematic reviews on the two concepts. 10 Again, the relationship was stronger when performance-based tests were used exclusively or in addition to other measures, as compared to measures based on (self-)perception. This is an important finding as research has previously shown that diabetes knowledge is related with successful self-management and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar fashion, we found that health literacy was positively related to diabetes knowledge, echoing findings from systematic reviews on the two concepts. 10 Again, the relationship was stronger when performance-based tests were used exclusively or in addition to other measures, as compared to measures based on (self-)perception. This is an important finding as research has previously shown that diabetes knowledge is related with successful self-management and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…4 These functional skills have been studied in the context of chronic diseases since the term health literacy first appeared in 1974, 5 and their relations to health outcomes, use of healthcare services, and costs have been repeatedly documented. 6 Concerning diabetes, a large body of empirical research assessing the relation between health literacy and diabetes-related knowledge, management, and outcomes has been summarized in numerous systematic and narrative reviews with heterogeneous results (e.g., [5][6][7][8][9] ) For example, Caruso and colleagues, 10 in their systematic review of six systematic reviews, concluded that, while the link between health literacy and diabetes knowledge is well-established, inconsistent findings exist for the relationships between health literacy and diabetes-related outcomes. To the best of our knowledge, only one metaanalysis on eight studies 11 investigated the role of health literacy in diabetes outcomes, focusing on health-literacy-sensitive interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, beliefs are defined as patients' concerns for treatment, and their understanding of the necessity of being treated with OAC [23]. Lastly, health literacy was defined as an individual's capacity to obtain, understand, and function the basic information and services to best manage his or her health, and engage in proper decision-making [24]. Previous research reported that anticoagulated patients with low health literacy were less adherent to OAC, exhibiting an increased risk of complication and disease-related mortality [25].…”
Section: Introductionmentioning
confidence: 99%
“…This case report shows a complex case of non‐healing sternal wound management in a patient with type 2 diabetes mellitus. Several factors could have affected the healing process over the course of the treatments, such as lifestyle and patient compliance, so it can be difficult to define which clinical change could be associated with the wound healing . However, the timing of consultation with the wound care specialist appears to reflect the traditional modus operandi in managing sternal wounds after cardiac surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors could have affected the healing process over the course of the treatments, such as lifestyle and patient compliance, so it can be difficult to define which clinical change could be associated with the wound healing. [8][9][10] However, the timing of consultation with the wound care specialist appears to reflect the traditional modus operandi in managing sternal wounds after cardiac surgeries. In fact, the wound care specialist, unlike other wounds (eg, pressure ulcers), did not initially assess the sternal wound because its treatment was initially managed without wound specialist consultation.…”
Section: Discussionmentioning
confidence: 99%